Influence of Substrate Concentration on Kinetic Parameters of Ethanol Dehydration in MFI and CHA Zeolites and Relation of These Kinetic Parameters to Acid-Base Properties - Čičmanec, Pavel; Kotera, Jiří; Vaculík, Jan; Bulánek, Roman (MDPI, 2022)
The catalytic activity of zeolites is often related to their acid-base properties. In this work, the relationship between the value of apparent activation energy of ethanol dehydration, measured in a fixed bed reactor and by means of a temperature-programmed surface reaction (TPSR) depending on the amount of ethanol in the zeolite lattice and the value of activation energy of H/D exchange as a measure of acid-base properties of MFI and CHA zeolites, was studied. Tests in a fixed bed reactor were unable to provide reliable reaction kinetics data due to internal diffusion limitations and rapid catalyst deactivation. Only the TPSR method was able to provide activation energy values comparable to the activation energy values obtained from the H/D exchange rate measurements. In addition, for CHA zeolite, it has been shown that the values of ethanol dehydration activation energies depend on the amount of ethanol in the CHA framework, and this effect can be attributed to the substrate clustering effects supporting the deprotonation of zeolite Bronsted centers.
Vliv substrátové koncentrace na kinetické parametry dehydratace etanolu na MFI a CHA zeolitech a vztah těchto parametrů k acido-bazickým vlastnostem
Keywords: chabazite; MFI; zeolite acid-base properties; ethanol dehydration; substrate clustering; temperature programmed surface reaction; chabazit; MFI; acido-bazické vlastnosti; TPSR